Ecologia populacional do bivalve Isognomon bicolor (C.B. ADAMS, 1945) no litoral do semiárido brasileiro - Nunes, Luysa Maria de Souza (2022)
Among marine ecosystems, coastal environments are one of the most susceptible to biological invasion. When sessile bivalves invade these ecosystems, they often form dense and extensive banks that reach a wide spatial scale and can have serious impacts on ecosystem health. An example of a sessile bivalve that has spread along the entire Brazilian coast is Isognomon bicolor. In Brazil, this Caribbean bivalve was first recorded in 2002. Over these two decades, several population studies were carried out along the entire coast; however, none of these studies were able to observe these populations at different times of the invasion. Thus, to understand the processes involved in biological invasions, two populations of I. bicolor at different stages of invasion were monitored between July 2018 and July 2019. In chapter I, the spatial and temporal distribution of these populations was analyzed. In chapter II, the population structure and dynamics of these populations were compared. The results of Chapter I revealed that the populations of the invasive bivalve have significantly different population densities. The spatial and temporal distribution of the invasive bivalve also occurred differently between the populations studied, confirming our hypothesis that the populations of the invasive bivalve vary according to the time of invasion. This population variation is described in the literature as a phenomenon called “boom-bust”, where populations of invasive species go through a period of population expansion, which usually occurs at the beginning of the invasion, followed by a marked population decline. In Chapter II, the structure and dynamics of populations of I. bicolor confirm that the oldest populations of this invasive bivalve are composed of larger individuals and are maintained by the longevity of adults. Recent populations have smaller individuals in their composition and are supported by intensive recruitment that overcomes the high mortality rates present in the population. Knowing that the invasion process is highly dynamic, continuous and long-term monitoring of these populations is important in order to elucidate the processes involved in biological invasions such as the boom-bust. Thus, the prevention and mitigation of impacts generated by invasive species can minimize the damage that these species can cause to biodiversity and ecosystem services.